HACE1: A Novel Repressor of RAR Transcriptional Activity - Zhao, Jianhua (2009)
The diverse biological actions of retinoic acid (RA) are mediated by RA receptors (RARs) and retinoid X receptors (RXRs). While the coregulatory proteins that interact with the ligand-dependent AF-2 in the E region are well studied, the ligand-independent N-terminal AF-1 domain-interacting partners and their influence(s) on the function of RARs are poorly understood. HECT domain and Ankyrin repeat Containing E3 ubiquitin-protein ligase (HACE1) was isolated as a RARβ(3) AB region interacting protein. HACE1 interacts with RARβ(3) both in in vitro GST pull-down and in cell-based coprecipitation assays. The interaction sites map to the N terminus of RARβ(3) and the C terminus of HACE1. HACE1 functionally represses the transcriptional activity of RARα(1), RARβ isoforms 1, 2 and 3, but not RARγ(1) in luciferase reporter assays. In addition, HACE1 represses the endogenous RAR-regulated genes CRABP II, RIG1 and RARβ(2), but not RAI3 in CAOV3 cells. Mutation of the putative catalytic cysteine (C876 of LF HACE1), which is indispensable for its E3 ubiquitin ligase activity, does not alter the repressive effect of HACE1 on the transcriptional activity of RARβ(3). On the other hand, HACE1 inhibits the RA dependent degradation of RARβ(3). It is possible that the repression of RAR-regulated transcription by HACE1 is due to its ability to inhibit the RA-dependent degradation of RARs.